Patient activation in adults with chronic conditions: A systematic review. (January 2021) - Newland, Pamela; Lorenz, Rebecca; Oliver, Brant J
Patient activation is an important aspect of self-management for adults with chronic non cancerous health conditions (CHC). However, there is limited evidence about which measures of patient activation and healthrelated quality of life are most useful to clinicians. This systematic review examined regarding the types of measures used to evaluate a patient's readiness for self-management including patient activation and healthrelated quality of life (HRQOL). Two such as measurements are the Patient Activation Measure (PAM) and overall PROMIS ® Global health. Ten articles were identified which included measurement of patient activation and HRQOL. The results indicate that HRQOL is evaluated with various measurement tools. Most researchers agree that patient activation and the measurement of global HRQOL positively contribute to successful self-management strategies.